TIME AND CONCENTRATION RELATIONSHIPS IN THE LONG-CHAIN REACTION OF GROUP A STREPTOCOCCI IN HOMOLOGOUS ANTISERUM AND AN IMPROVED METHOD FOR EVALUATION OF TEST RESULTS - Hahn, Jerome J. (1962)
Hahn, Jerome J. (National Institutes of Health, Bethesda, Md.) and Roger M. Cole. Time and concentration relationships in the long-chain reaction of group A streptococci in homologous antiserum and an improved method for evaluation of test results. J. Bacteriol. 83:85–96. 1962—We have described a statistically controlled method for evaluating the long chain reaction of group A streptococci grown in homologous antisera. The method is based on the chi-square analysis of the frequency distribution of chain lengths found in test and control sera, and is called the Size-Class Frequency method. Useful tables for rapid application of the method are presented. It is reproducible, and is simpler, more rapid, and more sensitive than the previously described method. Using this method, we have shown that the long-chain reaction reaches a maximum and then declines with time of incubation. The time at which the maximal response and height are attained depends directly on the initial antibody concentration and inversely on the initial antigen concentration. The inter-relationships of time, antibody concentration, total number of cocci, total number of chains, and long-chain frequency (or chain length) are presented in the discussion. In view of the findings reported here, we suggest a re-evaluation of possible methods of “dechaining” or “chaining” among group A streptococci. Present evidence appears inadequate to explain the long-chain reaction on the basis of inhibition of a single enzyme.